(3eWGdY GdCfhGQ Ydi UQGFM GdGKGQs - (3GHf bQbhd , EHQGgje Hf jhSa Hf GOge GdhgQGfj, CHh ESMGb,J (B569 (3g` s ((3jhSa Hf ehSi GdYeGdi s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3ceG MOKfG GdTjN Gdabjg GdMGaX CHh HcQ GdeYGaQi bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd (B" (3eVQ Gddg CeQAG SeY efG MOjKkG aMaXg MJi jHdZg ZjQg GdMOjK s
(3BNQgG (B:s
(3jfJgi HTQM ZQjH CMGOjK (B" (3Gdeje eY GdjGA(B" (3hBNQ eG ajg bhdg (B: (3hCeG TOGO Hf GdgGO aEfeG gh djKi dGfUQi abGd (B: (3ehdi TOGO Hf GdgGO ZjQ efShH ced GdChd ef GdeWGdY s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B129s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs